Measurements of top-quark pair to Z-boson cross-section ratios at s√=13,8,7 TeV with the ATLAS detector - Aad, G. (2016)
Ratios of top-quark pair to Z-boson cross sections measured from proton?proton collisions at the LHC centre-of-mass energies of s = 13 TeV, 8 TeV, and 7 TeV are presented by the ATLAS Collaboration. Single ratios, at a given s for the two processes and at different s for each process, as well as double ratios of the two processes at different s, are evaluated.The ratios are constructed using previously published ATLAS measurements of the t t  ̄ andZ-boson production cross sections, corrected to a common phase space where required, anda new analysis of Z → ` + ` − where ` = e, μ at s = 13 TeV performed with data collectedin 2015 with an integrated luminosity of 3.2 fb −1 . Correlations of systematic uncertaintiesare taken into account when evaluating the uncertainties in the ratios. The correlation modelis also used to evaluate the combined cross section of the Z → e + e − and the Z → μ + μ −channels for each s value. The results are compared to calculations performed at next-to-next-to-leading-order accuracy using recent sets of parton distribution functions. The datademonstrate significant power to constrain the gluon distribution function for the Bjorken-xvalues near 0.1 and the light-quark sea for x < 0.02.